Small states in a post-cold war world : stress and stability in the security strategies of Israel and Singapore. - Tan, Noel Eng Kiat. (2008)
This essay examines the effectiveness of the strategies Singapore and Israel have adopted in the post-Cold War environment, as they aim to have stability in new and stressful conditions. This study also highlights the degree to which their success can be replicated by other small states around the world.